DESAIN ALAT PROMOSI MULTIMEDIA PRODUK PT GRACIA KARYA MASEHI - Nurul Badriah (Narada : Jurnal Desain dan Seni, 2020)
Promotional tools are the initial media for corporate imagery as well as tools used in great opportunities to achieve sales & profitability of the company. PT Gracia Karya Masehi does not yet have a promotional tool on its behalf & so far the promotion process through the mother company (PT. Omega) is only by using a catalog (printed). Therefore, the purpose of this research is to design a new promotional tool for the better name of PT Gracia Karya Masehi, the design of multimedia product promotion tools (computerized based on animation). The research method approach conducted using data collection methods in the form of direct observation, interviews, literature, and surfing the internet as well as design analysis methods with a simple depiction of the proposed promotion system using Use Case & Activity diagrams. It can be concluded that the promotion of PT Gracia Karya Masehi can be simplified from its promotional systems such as promotions carried out by itself and the promotion tools developed by creating new promotional tools utilizing multimedia.